Indução de resistência à antracnose em feijoeiro por Trichoderma harzianum e Bacillus subtilis - Junges, Emanuele (2016)
The massive use of chemicals to control plant diseases cause numerous negative impacts on agricultural production system on non-target organisms, consumers and farmers. Therefore, the use of biological control organisms such as Trichoderma harzianum and Bacillus subtilis, able to act on the control of plant pathogens and / or induce resistance in plants is characterized as an important and with great potential yet to be explored tool. The objective of this study was to identify metabolites produced by these organisms grown in liquid medium and test the use of filtered culture and of living organisms, applied via seed or leaf in the control of anthracnose in beans. Biological control organisms T. harzianum and B. subtilis were grown in liquid culture medium for 96 h and 12 h photoperiod. After incubation, the media were filtered through Millipore membrane extraction of the bacterial cells and spores. Metabolites were extracted with four organic solvents, ethanol, methanol, ethyl acetate and hexane and subjected to gas chromatography and mass spectrometry and the chromatograms generated for each organism and solvent used. The evaluation of the induction of defense responses in plants was held in cultivating Minuano with susceptibility reaction to the pathogen Colletotrichm lindemuthianum. The bean plants were evaluated for disease index, area under the disease progress curve and changes in peroxidase activity, β-1,3-glucanase and IAA - oxidase, as well as certain fresh and dry weight of plants in two stages, before and after inoculation of the challenging pathogen. The chromatographic identification of compounds from culture filtrates showed that both test organisms produce fatty acids and oxylipins in liquid medium with antifungal action and inducing defense responses, respectively. In the assessments performed in bean plants, both T. harzianum as B. subtilis reduced the severity and progress of the disease, and produced significant increases in the activities of peroxidase isozymes and β-1,3-glucanase after inoculation of the pathogen, indicating the activation of induced resistance. The induction of responses did not affect the dry mass of the plants, which shows no energy expenditure that could affect plant growth. The best answers to T. harzianum are observed in foliar applications, either spore suspension or culture filtrate, as for B. subtilis, the best answers are observed in the foliar application of culture filtrate. For ease of production, culture filtrates of Trichoderma harzianum and Bacillus subtilis can give bioproducts for agricultural use.